2017
DOI: 10.3390/ijerph14111351
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Airborne Particulate Matter on Respiratory Health in a Community near a Cement Factory in Chilanga, Zambia: Results from a Panel Study

Abstract: We conducted a panel study to investigate seasonal variations in concentrations of airborne PM2.5 and PM10 and the effects on respiratory health in a community near a cement factory; in Chilanga; Zambia. A panel of 63 and 55 participants aged 21 to 59 years from a community located at the edge of the factory within 1 km and a control community located 18 km from the factory respectively; were followed up for three climatic seasons July 2015 to February 2016. Symptom diary questionnaires were completed and lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 37 publications
(55 reference statements)
3
31
0
1
Order By: Relevance
“…Similar studies have found that children attending schools near cement factories among other industrial sources were more vulnerable to higher levels of PM 2.5 . 42 Although the wind speed was positively correlated with PM, PM 2.5 levels were reduced by 24.8% in classrooms compared to those in outdoor air. This could be due to the windows and doors of school E which were facing upwind, allowing less infiltration of particles.…”
Section: Discussionmentioning
confidence: 92%
“…Similar studies have found that children attending schools near cement factories among other industrial sources were more vulnerable to higher levels of PM 2.5 . 42 Although the wind speed was positively correlated with PM, PM 2.5 levels were reduced by 24.8% in classrooms compared to those in outdoor air. This could be due to the windows and doors of school E which were facing upwind, allowing less infiltration of particles.…”
Section: Discussionmentioning
confidence: 92%
“…Our results indicate that living in close proximity to quarry sites, which is a main source of dust, is a potential factor for increasing the prevalence of eye and respiratory symptoms. It has been found that dust is one of the most invasive and potentially irritating sources for the eyes and respiratory system [ 14 , 15 , 36 ]. Research has shown that dust concentration, deposition rates, and potential impacts tend to decrease rapidly away from the dust source [ 3 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, dust was noted as a trigger for allergic rhinitis (Adegbiji et al, 2018) and house dust/dust mite exposure was associated with asthma (Bardei et al, 2016;Flatin et al, 2018). Particulate matter was evaluated in 24 of the indoor air pollution research studies, most focusing on PM10 (Abou-Khadra, 2013;Ibhafidon et al, 2014;Makamure et al, 2016;Jafta et al, 2017;Nkhama et al, 2017;Nkosi et al, 2017;Mentz et al, 2018) and PM2.5 exposures (Oluwole et al, 2013;Chafe et al, 2014;Ibhafidon et al, 2014;Dutta et al, 2017;Lacey et al, 2017;Lin et al, 2017a;Malley et al, 2017;Nkhama et al, 2017;Wylie et al, 2017a;Wylie et al, 2017b;Mentz et al, 2018). Some studies also measured NO, NO2, SO2, CO, and O3 (Jafta et al, 2017;Wylie et al, 2017a).…”
Section: Exposures Measuredmentioning
confidence: 99%